Asupan omega-6 dan kejadian persalinan caesarean section di wilayah Puskesmas Bendosari - Fitriana Mustikaningrum; Anindya Rahmaningtyas; Nur Lathifah Mardiyati; Dwi Sarbini (Nutrition Scientific Journal, 2023)
The prevalence of Cesarean Section (SC) childbirth in the Bendosari Health Center area is quite high, namely p in 2022 from January to March as much as 28.68% of the total 122 deliveries. One of the factors that cause cesarean section is PUFA intake, especially high omega-6 intake. This study aims to determine the relationship between omega-6 intake and the incidence of cesarean section in postpartum mothers in the Bendosari Health Center area. This study was used an observational method with a cross sectional approach. The subjects of the study were 66 postpartum mothers and purposive sampling method was used because the number of postpartum mothers who have infants less than 3 months and had history of SC not by their will, not due to short birth spacing, not placenta previa and infection was limited. Sampling of postpartum mothers with infants 3 months of age is done with the aim of observing omega-6 consumption in the 2nd and 3rd trimesters. Data on omega-6 intake during the 2-3rd semester tri pregnancy period were obtained by direct interview method using the Semi Quantitative Food Frequency (SQ-FFQ) form while data method of delivery was obtained through secondary data from Bendosari Primary health care. The association between omega-6 intake and the incidence of SC birth was analyzed using the Chi Square test. There was no relationship between omega-6 intake and the incidence of SC in the Bendosari Health Center area (P-value= 0.96). Keywords: omega-6 intake, cesarean section, pregnancy